Synthesis and stimuli-responsive properties of the phenanthroline based metallo-supramolecular polymers - Demirel, Maruf Hursit; Koytepe, Suleyman; Gultek, Ahmet; Seckin, Turgay (Springer, 2014)
A series of functional metallo-supramolecular materials based on polyhedral oligomeric silsesquioxane (POSS) and phenanthroline ligand were prepared using a two-step approach. Firstly, using a phenanthroline ligand, an amino-functionalized transition metal complex was prepared by tin(II) chloride. In the second step, this metal complex was subsequently reacted with the octakis(3-chloropropyl)octasilsesquioxane, resulting for the metallosupramolecular polymers bearing POSS structure. All the synthesized compounds were fully characterized by spectroscopic analysis, thermal and electron microscopy techniques. Stimuli responsible properties of metallo-supramolecular materials were also investigated the reversibility upon external factors, such as electrochemical or the addition of competitive complexing ligands by electroanalytic techniques and UV-Vis spectroscopy. The electro- and chemo-responsive properties of the metallo-supramolecular materials were also improved. As a result, prepared phenanthroline-functionalized polyhedral silsesquioxane are good candidates for electronic, opto-electronic, and photovoltaic applications as a smart stimuli-responsive material.
Keywords: Supramolecular polymers; Stimuli-responsive polymers; POSS; Phenanthroline ligands